Novel mediators regulating innate and adaptive type 17 immune responses - Russell, Shane E. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2014)
The discovery of a third subset of T helper cells and more recently innate T cell subsets which preferentially express IL-17A has led to intensive investigation into the roles these cells play in both host defence and autoimmune settings As such, understanding the mechanisms related to the of the generation, function and regulation of these cells are crucial to the development of therapeutic interventions to counteract associated inflammation and pathology. In these studies we have focused on two of the more recently described pathways of regulation of IL-17A expressing T cells, namely the IL-2/IL-2 receptor signalling axis and TIR8 a negative regulator oflL-1R1 signalling.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin